An evaluation of mathematics learning program at primary education using Countenance Stake Evaluation model - Bayuk Nusantara Karaeng Jannang Tompong; Jailani Jailani (Jurnal Penelitian dan Evaluasi Pendidikan, 2019)
The quality of mathematics learning in Bantaeng Regency, South Sulawesi were in a low category based on the research findings from the Institute of Educational Quality Assurance of South Sulawesi in 2011. It affects students to be unwilling to be involved in the process of mathematics learning. This study aims to evaluate the process of learning mathematics in the elementary educational level at Bantaeng Regency. The model of evaluation used in this study is the Stake Countenance Model consisting of three steps of evaluation, namely antecedent, transaction, and outcomes. The subjects of this study were 12 teachers at state elementary schools in Bantaeng Regency assessed by three raters. There were 363 midterm score tests from 12 schools. The instruments used in this study were observation sheet, lesson plan sheet, assessment documentation sheet, and interview guideline. This study used a quantitative research approach supported by qualitative data. The result of the study shows that (1) the lesson plan of mathematics subject is in a good category (93.45%), (2) the learning process is in the good enough category (67.07%), (3) the document of students assessment is in the good enough category (71.34%), and (4) most students in each school do not pass the school standard.